2021
DOI: 10.1186/s12902-021-00820-8
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of FAM19A5 are inversely associated with subclinical atherosclerosis in non-alcoholic fatty liver disease

Abstract: Background Family with sequence similarity 19 (chemokine (C-C motif)-like) member A5 (FAM19A5) is a newly identified adipokine. There is a limited number of studies linking FAM19A5 to metabolic disorders. In the current study, we aimed to explore if FAM19A5 is associated with nonalcoholic fatty liver disease (NAFLD). We also sought to determine the possibility of FAM19A5 association with subclinical atherosclerosis in NAFLD patients. Methods A tota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Yari et al [21] reported a lower plasma FAM19A5 concentration in patients with NAFLD than the controls and a significantly negative correlation between plasma FAM19A5 levels and BMI; meanwhile, there was no relationship between FAM19A5 and FBG in an adult cohort [6, 21]. Notably, Lee et al [6] and Yari et al [21] did not include fasting insulin data of their subjects. Therefore, a comprehensive study with more indicators of IR should be conducted.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yari et al [21] reported a lower plasma FAM19A5 concentration in patients with NAFLD than the controls and a significantly negative correlation between plasma FAM19A5 levels and BMI; meanwhile, there was no relationship between FAM19A5 and FBG in an adult cohort [6, 21]. Notably, Lee et al [6] and Yari et al [21] did not include fasting insulin data of their subjects. Therefore, a comprehensive study with more indicators of IR should be conducted.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Children with obesity are more prone to complications with cardiovascular diseases than their normal peers [25]. Considering the cardioprotective roles of FAM19A5 and FSTL1 in adults, our research also aimed to investigate the role of the two adipokines in obesity and obesity-associated vascular endothelial injury in children [5, 21, 26, 27]. ox-LDL induces apoptosis of endothelial cells, is involved in endothelial dysfunction, and promotes endothelial injury.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…TAFA5 , CPB1 , and SLCO1B3 were the hub genes in the grey60 module. TAFA5 , also known as FAM19A5 , plays a protective role in atherosclerosis, obesity and inflammation [ 56 ]. As a new fat protective factor, TAFA5 can inhibit the proliferation, migration and neointima formation of vascular smooth muscle cells after injury [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“… Xia Lei et al, 2019 56 Cells from Eight-week-old C57BL/6J male mice Expression of FAM19A5 in various areas of the mouse brain is induced or suppressed by undernutrition and nutritional states. In male mice, FAM19A5 deficiency altered food intake patterns during the light-dark cycle Fatemeh Ali Yari et al, 2021 57 Total of 69 subjects including 37 NAFLD and 32 control subjects The plasma FAM19A5 concentration in NAFLD patients was significantly lower in NAFLD patients compared with the control group. significant negative correlations were observed between plasma FAM19A5 levels and BMI, visceral fat, ALT, AST, LS, and cIMT Wesołek A. et al, 2022 58 45 people with MetS, 35 healthy people without MetS There were no differences in the blood levels of FAM19A5 between the groups.…”
Section: Fam19a5 Original Direction Of Researchmentioning
confidence: 98%